ANALISIS STRATEGI GURU DALAM MEMOTIVASI BELAJAR PESERTA DIDIK PADA PEMBELAJARAN SEJARAH DI KELAS XI SMAN 5 PONTIANAK - Charles Ritonga; Aminuyati Aminuyati; Ika Rahmatika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The aim of this research was aimed at obtaining information and clarity about theanalysis of teacher strategies in motivating students' learning in class XI of SMAN 5Pontianak. This study used a qualitative research method with a descriptive form.Sources of data in this study were teachers of history subjects, waka curriculum, studentsand data in the form of interviews. Research results showing that. (1) On the learningdevice the teacher has inserted learning motivation in the preliminary and core learningactivities. (2) The application of motivating students' learning is carried outspontaneously in line with the delivery of learning materials. As for what must beconsidered, namely the readiness of students to receive learning. When students areready to accept learning, the motivation given will be easily accepted. As well as thedelivery of learning objectives to be studied, will make it easier for students to know andunderstand learning. (3) The teacher's obstacle in motivating students' learning is foundin the students themselves, where there are students who have low interest in learning. (4)The solution to overcome the obstacles to students' learning motivation, the teacherprovides individual motivation to students with low motivation, and provides views andadvice.Keywords: Learning motivation, Learning strategy, Students